KAJIAN SINTAKSIS DALAM PENGGUNAAN FRASA DI JEJARING SOSIAL FACEBOOK - Gosita Ifantias Meisawitri; Luluk Isani Kulup (Buana Bastra, 2018)
Every human being would socialize with other humans. Humans interact by using a tool called language. Language itself is often inerpreted as arbitrary system sounds symbol, languageis universal, that language has meaning or has intention to nonvey something. Language as a meansof social communication can be illustrated in the social network facebook. The phrase is notpredicative and does not have verb and phrases are groups of words. The phrase can be dividedinto phrases and phrases eksosentrik and endosentrik. The use of the phrase alone is consideredless sufficiet when used to make facebook social media users use the appropriate phrase. Facebookuser community consists of some society levels, the top level society, middle level society andbottom level society. Many Facebook users do not care about it because each of them has a styleand language in their own words. No exception educated people, for example, teachers also use alot of slang phrase because era development factors which one of them is language. This studyused a qualitative approach because the research aimed to explain itself and to describe errors ofphrase using that appear in the facebook social media. This research data was screenshot of thestatus sentences .The data source was facebook. Based on the findings of the data and data analysis,it is found some the use of noun phrase, verb phrase, the adjecive phrase, numeralia phrases andprepositional phrase as its function in facebook. According to Samsuri, There are five kinds ofphrases: (1) noun phrase, (2) verb phrase, (3) the adjective phrase, (4) the numeralia phrase, and(5) prepositional phrase. Thus, it can be concluded that there are some the use of phrase thatappears in the status which is written by facebook users.